Brand Image as a Determinant of Student and Parent Satisfaction: Insights From Public Madrasah Aliyah in Pekanbaru - Rini Setyaningsih; Irawati; Mahdini Al Ghifari; Arrum Intan Sari (Institut Agama Islam An-Nawawi Purworejo, 2025)
The high competition between educational institutions encourages madrasas to build a strong school brand image as a strategy to attract and maintain stakeholder satisfaction, especially students and parents. This study aims to analyze the influence of school brand image on student and parent satisfaction in State Madrasah Aliyah (MAN) throughout Pekanbaru City. The method used is quantitative with an associative approach. The sample consisted of 668 respondents (334 students and 334 parents) from MAN 1 and MAN 2, selected through a purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using validity (Pearson), reliability (Cronbach's Alpha), normality (Kolmogorov-Smirnov), linearity, homogeneity, Spearman's rho correlation, and coefficient of determination. The results show that perceptions of school brand image are in the category of quite good according to students (M = 81.06) and very good according to parents (M = 95.13). Student satisfaction was quite good (M = 76.98), while parental satisfaction was very high (M = 51.68). There was a significant influence between school brand image on student satisfaction (ρ = 0.662; Sig. = 0.000) and parents (ρ = 0.189; Sig. = 0.000), with contributions of 43.8% and 3.57%, respectively. These findings support the theory of Aaker, Keller, and Zeithaml regarding the role of institutional image in shaping satisfaction. Academically, this study broadens the understanding of brand management in the context of Islamic education, and practically provides input for madrasas in developing service strategies based on stakeholder perceptions.